KONSEP ILMU MENURUT MUHAMMAD BIN ABDUL WAHHAB DALAM KITAB MATAN AL-USHUL ATS-TSALATSAH - Muhammad Muchtar Lubis; Muslimah Muslimah; Muhammad Rifai Harahap (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2021)
AbstractThe knowledge that must be known and studied by a Muslim is the science of monotheism, knowing Allah Almighty, the Prophet Muhammad, and Islam, this knowledge will save the world and the hereafter. The research objective was to analyze the concept of science according to Muhammad bin Abdul Wahhab in the book of contents Al-Ushul Ats-Tsalatsah. A qualitative approach with the type of research library research and discourse analysis techniques. The research findings show that the knowledge according to Muhammad bin Abdul Wahhab is divided into three. First, knowing Allah, namely knowing Allah is the Rabb who must be worshiped to carry out orders and stay away from His prohibitions, and not associate with Allah. Knowing Allah through His signs of power, namely night, day, sun, and moon, as well as His creation, namely the seven layers of heaven and earth. Second, knowing the Prophet Muhammad, knowing his lineage, age, place of birth and place of migrating, his 23 years of prophetic life, and the purpose for which he was sent. Third, knowing Islam, namely surrendering to Allah by affirming Him, freeing oneself from shirk, and knowing the three levels of Islam, namely: Islam, faith, and Ihsan. There are five pillars of Islam, six pillars of faith, and ihsan have one pillar.Keywords: Al-Ushul Ats-Tsalatsah; Konsep Ilmu; Muhammad Bin Abdul Wahhab. AbstrakIlmu yang wajib diketahui dan dipelajari seorang muslim adalah ilmu ketauhidan, mengenal Allah swt., Nabi Muhammad saw. dan agama Islam, ilmu inilah yang akan menyelamatkan di dunia dan akhirat. Tujuan penelitian menganalisis konsep ilmu menurut Muhammad bin Abdul Wahhab dalam kitab matan Al-Ushul Ats-Tsalatsah. Pendekatan kualitatif dengan jenis penelitian library research dan analisis teknik wacana discourse analysis. Temuan penelitian bahwa ilmu menurut Muhammad bin Abdul Wahhab terbagi tiga. Pertama, mengenal Allah yaitu mengetahui  Allah adalah Rabb yang harus diibadahi melaksanakan perintah dan menjauhi larangan-Nya, serta tidak menyekutukan Allah. Mengetahui Allah melalui tanda kekuasaan-Nya yaitu malam, siang, matahari dan bulan, juga ciptaan-Nya yaitu tujuh lapis langit dan bumi. Kedua, mengenal Nabi Muhammad saw., mengetahui nasab, umur, tempat kelahiran dan tempat hijrah, kehidupan kenabiannya selama 23 tahun, serta tujuan ia diutus. Ketiga, mengenal Islam yaitu berserah diri kepada Allah dengan mengesakan-Nya, membebaskan diri dari kesyirikan dan mengetahui tiga tingkatan agama Islam, yaitu: Islam, iman, dan ihsan. Rukun Islam ada lima, rukun iman ada enam dan ihsan memiliki satu rukun. Kata Kunci: Al-Ushul Ats-Tsalatsah; Konsep Ilmu; Muhammad Bin Abdul Wahhab